Nanocompósitos biocompatíveis de poliuretana com hidroxiapatita e nanocelulose - Arantes, Thaís Moraes (2018)
Polyurethane nanocomposites were prepared with nanoparticles of hydroxyapatite and/or nanocellulose in order to obtain biocompatible materials. The nanocelluloses were obtained from sugarcane bagasse, seeking to evaluate their use as a source of cellulose nanofibers. The conditions of extraction and separation of the nanocelluloses were investigated. The effect of time and concentration of sulfuric acid was studied, resulting in particles with reduced size and homogeneity in the size distribution without cellulose degradation. The cellulose nanocrystals that presented the best results regarding suspension staining, crystallinity index, thermal properties, particle size and Zeta potential were those hydrolyzed in 50% H2SO4 at 45 ° C for 2 hours. For the synthesis of the hydroxyapatite (HA) nanoparticles, a multivariate statistical analysis was carried out using a factorial design with resolution 23 . From which an empirical model was created that allows the control of the shape and size of the hydroxyapatite nanoparticles. HA nanoparticles with sizes varying from 8 nm to 600 nm were formed by oriented coalescence growth mechanism. The structure was confirmed by images of Electron Transmission Electron Microscopy and Scanning Electron Microscopy. The hydroxyapatite nanoparticles presented a well-defined nanorod shape with a narrow size distribution. It was observed that the model was statistically significant and the main parameter for the growth of crystals in the hydrothermal process was the temperature. Polyurethanes derived from castor oil were synthesized without residues of their monomers. The insertion of the nanoparticles into the polymer matrix improved the thermal stability of the composite. Finally, the cell viability assay showed that polyurethane nanocomposites with hydroxyapatite are biocompatible and in this way can be used as biomaterial.